Dibenzopleiadiene-embeded polyaromatics: Via [4 + 3] annulative decarbonylation/decarboxylation - Kritchasorn Kantarod (2022)
A novel strategy is developed for the synthesis of dibenzopleiadiene-embedded polycyclic aromatic hydrocarbons from 1,8-naphthalic anhydride derivatives and cyclic diaryliodonium salts through a palladium-catalyzed cascade [4 + 3] decarbonylative/decarboxylative annulation. The mechanism of the reaction is proposed and the molecular structure, photophysical properties, and frontier molecular orbitals of diverse dibenzopleiadiene-embedded polyaromatics are elucidated by X-ray crystallography, UV-Vis and fluorescence spectroscopy, and DFT calculations.